Integrated farming systems for prosperity of marginal farmers and sustainable agriculture: a roadmap for India - BEHERA, U K (The Indian Journal of Agricultural Sciences, 2019)
Agriculture in India and other Asian countries is facing multiple and complex challenges which are expected to become severe with the passage of time. Some major challenges are sustainability of natural resources, impact of climate change and decline in factor productivity. Besides, declining trend in size of land holding poses a serious challenge to the profitability and sustainability of farming. In view of the decline in per capita availability of land, it is imperative to develop strategies and agricultural technologies that enable adequate employment and income generation, especially for smallholders (farmers with < 2.0 ha land) who constitute the vast majority of the farming community in the developing world. No single farm enterprise, such as a typical monocropping system, is likely to be able to sustain the smallholder farmer. Integrated farming systems (IFS) are less risky if managed efficiently, as they benefit from synergisms among enterprises, diversity in produce, and environmental soundness. On this basis, IFS have been suggested for the development of small and marginal farms across Asia, and researchers have developed strategies which have benefitted smallholder farmers by providing additional income and employment and minimizing risk. However, these IFS have not been promulgated and promoted effectively. The present review helps solve this by providing comprehensive information on innovative concepts, approaches and strategies for promotion of IFS for small-holder farmers, which is lacking at present.